Communication without borders - Breinstrup, Thomas (Language at Work - Bridging Theory and Practice, 2008)
Globalization demands an extra key to international communication. A living language with well-known words and a grammar without exceptions is already serving the needs of many people both privately and in business. But Interlingua is ready to unlock more doors to the world.